Engineering the properties of D-amino acid oxidases by a rational and a directed evolution approach - Pollegioni, Loredano; Sacchi, Silvia; Caldinelli, Laura; Boselli, Angelo; Pilone, Mirella S; Piubelli, Luciano; Molla, Gianluca (Current protein & peptide science, 2007)
D-amino acid oxidase (DAAO) is a FAD-containing flavoprotein that dehydrogenates the D-isomer of amino acids to the corresponding imino acids, coupled with the reduction of FAD. The cofactor then reoxidizes on molecular oxygen and the imino acid hydrolyzes spontaneously to the alpha-keto acid and ammonia. In vitro DAAO displays broad substrate specificity, acting on several neutral and basic D-amino acids: the most efficient substrates are amino acids with hydrophobic side chains. D-aspartic acid and D-glutamic acid are not substrates for DAAO. Through the years, it has been the subject of a number of structural, functional and kinetic investigations. The most recent advances are represented by site-directed mutagenesis studies and resolution of the 3D-structure of the enzymes from pig, human and yeast. The two approaches have given us a deeper understanding of the structure-function relationships and promoted a number of investigations aimed at the modulating the protein properties. By a rational and/or a directed evolution approach, DAAO variants with altered substrate specificity (e.g., active on acidic or on all D-amino acids), increased stability (e.g., stable up to 60 degrees C), modified interaction with the flavin cofactor, and altered oligomeric state were produced. The aim of this paper is to provide an overview of the most recent research on the engineering of DAAOs to illustrate their new intriguing properties, which also have enabled us to pursue new biotechnological applications.